2015
DOI: 10.1108/ijsms-16-03-2015-b002
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for the adoption of smartphones in a sports context

Abstract: This study proposes a conceptual model to comprehensively understand how sports fans perceive and accept smartphones and applications in a sport consumption context by developing a series of propositions. Theoretically based on the Technology Acceptance Model (TAM) and the Sport Website Acceptance Model (SWAM), this study provides fundamental groundwork to better conceptualise sports fans' decision making processes involving the latest technology used to consume sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Ha et al [42] found no influence of PE on ITU, but the authors felt that while it was not related to ITU, it was related to PEOU, allowing sports consumers to undermine the difficulty of using the technology [71]. These results highlight the hedonic motives of sports consumers who often overlook entertainment [26,65,71] and may make the App more interesting to sports fans if they find it fun and easy to use. On the other hand, PT has been found to be an important and influential factor on ITU [1,38,39,53,69]; this importance may be motivated by the fact that if a sports fan finds the information they receive useful and reliable they will show a greater interest in continuing to use the technology.…”
Section: Discussionmentioning
confidence: 94%
“…Ha et al [42] found no influence of PE on ITU, but the authors felt that while it was not related to ITU, it was related to PEOU, allowing sports consumers to undermine the difficulty of using the technology [71]. These results highlight the hedonic motives of sports consumers who often overlook entertainment [26,65,71] and may make the App more interesting to sports fans if they find it fun and easy to use. On the other hand, PT has been found to be an important and influential factor on ITU [1,38,39,53,69]; this importance may be motivated by the fact that if a sports fan finds the information they receive useful and reliable they will show a greater interest in continuing to use the technology.…”
Section: Discussionmentioning
confidence: 94%
“…Research methods. The research used a questionnaire developed by Ha, Kang, and Ha (2015), which consisted of several partsdetermination of physical activity, usage of sports apps, user innovativeness, attachment to a smart device, the need for interaction, perception of sports apps (usefulness, ease of use, pleasure, and reliability) and further intentions to use the apps. Each of the factors had several questions which had to be evaluated using a 5-point Likert scale from 1 (totally disagree) to 5 (totally agree).…”
Section: Methodsmentioning
confidence: 99%
“…According to researchers, innovativeness is one of the most important personality traits that determines the desire to try new technologies (Kim et al, 2017;Okumus, Ali, Bilgihan, & Ozturk, 2018). Therefore, researchers Ha, Kang, and Ha (2015) have developed an improved version of the model that focuses not only on commonly considered important factors but more broadly examines the factors that stimulate intentions to use sports apps. As this model extensively examines the adoption of smart devices using it, we aim to elucidate the use of sports apps through their perception, personal user characteristics, and relationship with the smart device.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the TAM has been one of the most traditionally used models in professional settings thanks to its great robustness and applicability [ 9 , 46 ], paying special attention to the utilitarian aspect of the technology [ 47 ] and with the intention of understanding the consumer’s intention to use it [ 48 ]. The model has shown its utility by explaining the use of mobile technology in different contexts such as finance, instant messaging, healthcare, gambling, and tourism [ 9 ].…”
Section: Literature Reviewmentioning
confidence: 99%